Regional impact of exposure to a polychlorinated biphenyl and polychlorinated dibenzofuran mixture from contaminated rice oil on stillbirth rate and secondary sex ratio - Takashi Yorifuji (Environment International, 2013)
Yusho disease, a polychlorinated biphenyl (PCB) and polychlorinated dibenzofuran (PCDF) mixed poisoning caused by contaminated rice oil, occurred in Japan in 1968. The evidence on reproductive outcome is limited. We therefore evaluated the regional impact of the exposure to the PCB and PCDF mixture on stillbirth rate and secondary sex ratio among the residents in two severely affected areas. We selected the regionally-affected towns of Tamanoura (n = 4390 in 1970) and Naru (n = 6569) in Nagasaki Prefecture, Japan, for study. We obtained data on stillbirths (spontaneous/artificial) and live-born births (total/male/female) from 1958 to 1994. For a decade and a half after the exposure, an increase in the rate of spontaneous stillbirths coincided with a decrease in the male sex ratio. Compared with the years 1958–1967, the ratios for spontaneous stillbirth rates were 2.16 (95% confidence interval: 1.58 to 2.97) for 1968–1977 and 1.80 (95% confidence interval: 1.25 to 2.60) for 1978–1987. The sex ratio (male proportion) was 0.483 (95% confidence interval: 0.457 to 0.508) in the first 10 years after exposure. Exposure to a mixture of PCBs and PCDFs affected stillbirth and sex ratio for a decade and a half after the exposure. Keywords: Dioxins, Food contamination, Polychlorinated biphenyls, Sex ratio, Stillbirth, Yusho disease